2016
DOI: 10.1186/s12864-016-2662-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SSR-based association mapping for fiber quality in nation-wide upland cotton inbreed cultivars in China

Abstract: BackgroundSince upland cotton was introduced into China during the 1920s–1950s, hundreds of inbreed cultivars have been developed. To explore the molecular diversity, population structure and elite alleles, 503 inbred cultivars developed in China and some foreign cultivars from the United States and the Soviet Union were collected and analyzed by 494 genome-wide SSRs (Simple Sequence Repeats).MethodsFour hundred and ninety-four pairs of SSRs with high polymorphism and uniform distribution on 26 chromosomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 57 publications
9
89
1
Order By: Relevance
“…In previous studies, a large number of association analyses of fiber quality traits and SSR markers in upland cotton have been reported13143637. However, these studies were limited by the number of the polymorphic SSR markers and the size of the natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a large number of association analyses of fiber quality traits and SSR markers in upland cotton have been reported13143637. However, these studies were limited by the number of the polymorphic SSR markers and the size of the natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…In cotton, a few genetic studies using GWAS have been reported [2, 4, 23, 24]. Very recently another two GWAS papers in cotton have been published [25, 26]. All of those studies were based on using simple sequence repeat (SSR) markers.…”
Section: Introductionmentioning
confidence: 99%
“…Although scientists have successfully identified marker-trait associations using GBS-based SNPs in many plant species [14, 21, 28, 29], so far no GWAS study has been reported in Upland cotton using SNPs. There are a few GWAS studies that were reported using SSR markers in Upland cotton [2, 4, 23, 24, 26, 30] as mentioned earlier. Among those reports, our laboratory previously identified 131 fiber QTL and 37 QTL clusters using 1582 SSR markers and 275 RILs of the same MAGIC population [4].…”
Section: Introductionmentioning
confidence: 99%
“…The fast development of molecular maker technology has made it possible to map QTL for fiber quality and yield traits and to aggregate excellent genes controlling cotton yield and fiber quality using marker-assisted selection (MAS). The genome of upland cotton is complex and large [21], and the genetic background of upland cotton is narrow [22]. These reasons hinder the development of QTL mapping in upland cotton.…”
Section: Introductionmentioning
confidence: 99%